Audio Signal Encryption using Recursive Backstepping Technique for Tracking Controlling and Synchronizing Improved Sprott-C Hyperchaotic Systems - Murugan, J.; Muthukumar, P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, recursive backstepping control method for tracking control and synchronization of five-dimensional hyperchaotic improved Sprott-C systems are investigated. Based on synchronized hyperchaotic improved Sprott-C systems, a new secure technique for encrypting audio signals is put forth. The efficiency of the suggested synchronization and control strategies is confirmed by numerical simulations. We demonstrate that there is no difference between the original and decrypted audio signals by quantitatively validating the suggested encryption scheme.